Activités prostitutionnelles et gestion des violences : « les risques du métier » - Àgi Földhàzi (Genre, Sexualité et Société)
Sex work is mostly carried out by women or feminine-looking persons. They are potential victims of violence, both in their private life and in their working sphere - because of their working conditions and the stigma attached to prostitution. The expressions of violence are not specific to sex work, yet they are amplified by an accumulation of specific risk factors. Sex workers must monitor the information relative to their trade to avoid to be discredited by the "whore stigma". Based on a qualitative study, this article analyses the impact of stigmatisation of the sex workers on the resources they use to fight violence.